The optimal dose of oxycodone in PCIA after laparoscopic surgery for gastrointestinal cancer in elderly patients: A randomized controlled trial - Zhou, Yanjun; Huang, Xinyi; Chang, Huan; Sun, Hongyu; Xie, Wenxiu; Pan, Ziye; Zhang, Fan; Liao, Qin (Frontiers in Surgery, 2023)
Objective: To explore the optimal bolus dose of oxycodone for patient controlled intravenous analgesia (PCIA) without background dose in elderly patients after laparoscopic surgery for gastrointestinal cancer. Methods: In this prospective, randomized, double-blind, parallel-controlled study, we recruited patients aged 65 years or older. They underwent laparoscopic resection for gastrointestinal cancer and received PCIA after surgery. Eligible patients were randomly divided into 0.01mg/kg, 0.02mg/kg or 0.03mg/kg group according to the bolus dose of oxycodone in PCIA. The primary outcome was VAS scores of pain on mobilization at 48h after surgery. Secondary endpoints included the VAS scores of rest pain, the total and effective numbers of press in PCIA, cumulative dose of oxycodone used in PCIA, the incidence of nausea, vomiting and dizziness, as well as patients’ satisfaction at 48h after surgery. Results: A total of 166 patients were recruited and randomly assigned to receive a bolus dose of 0.01 mg/kg (n=55), 0.02 mg/kg (n=56) or 0.03 mg/kg (n=55) of oxycodone in PCIA. The VAS scores of pain on mobilization, the total and effective numbers of press in PCIA in 0.02 mg/kg group and 0.03 mg/kg group were lower than those in 0.01 mg/kg group (P < 0.05). Cumulative dose of oxycodone used in PCIA and patients’ satisfaction in 0.02 mg/kg and 0.03 mg/kg groups were more than those in 0.01 mg/kg group (P < 0.01). The incidence of dizziness in 0.01mg/kg and 0.02mg/kg groups was lower than that in 0.03mg/kg group (P < 0.01). There were no significant differences in VAS scores of rest pain, the incidence of nausea and vomiting among three groups (P > 0.05). Conclusion: For elderly patients undergoing laparoscopic surgery for gastrointestinal cancer, 0.02 mg/kg bolus dose of oxycodone in PCIA without background infusion may be a better choice.